Antioxidant Activity of The Successive Extracts of Tagetes erectus Flowers - CHAKRABORTHY, G.S. (Asian Journal of Chemistry, 2010)
Plants are the best source of active secondary metabolites which are beneficial to mankind. Many plant origin drugs have been reported with biological properties like analgesic, antiinflammatory, antioxidant, hypoglycemic agents and many more. The successive extracts of Tagetes erectus flowers were screened for in vitro antioxidant properties using the standard procedures. The successive extracts such as petroleum ether, ethyl acetate, methanol and water and 50 % crude methanol extracts exhibited IC50 values of respectively in DPPH and respectively in nitric oxide radical inhibition assays. The values are comparable with the standards such as ascorbic acid and quercetin. Tagetes erectus flowers are showing antioxidant activity.